Calculation of Health Service Rate Using Activity-Based Costing Method At Laboratory Installation of RSUP Dr. Tadjuddin Chalid Makassar - Mohammad Normansyah; Fatmawati Fatmawati (International Journal of Economics, Business and Innovation Research, 2022)
The aim of study is to calculate the health services rate at the laboratory installation of RSUP Dr. Tadjuddin Chalid Makassar by using the Activity-Based Costing method and comparing it with the rates that apply at the hospital, the results which can assist hospital management in determining new service rate patterns. The data used are primary data and secondary data. The method used is quantitative descriptive analysis, namely analyzing data by describing the data that has been collected using the Activity-Based Costing method. The results of the study show that there is a difference between the rates calculated using the Activity-Based Costing method and those applicable in hospitals due to cost distortion. There are 7 out of 10 services that are calculated to generate rates that are lower than the applicable rates (overcosting) with differences ranging from IDR 444 – IDR 48,567. Meanwhile, the other 3 services generate rates that are higher than the applicable rates (undercosting) with a difference of IDR 5,600 – IDR 11,835.